Pengembangan LKPD Berbasis Discovery Learning Berbantuan Software Tracker Untuk Meningkatkan Pemahaman Konsep Peserta Didik Kelas X di SMA Sriguna Palembang Pada Materi GHS - Sela Melinia; Patricia H.M Lubis; Sulistiawati Sulistiawati (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2021)
This study aims to produce LKPD products based on Discovery Learning assisted by Software Tracker to improve understanding of the concepts of class X students at SMA Sriguna Palembang that are valid, practical, and have a potential effect on understanding concepts. This study uses a modified Rowntree development model based on formative evaluation. The subjects used in this research are students of class X IPA 2 SMA Sriguna Palembang, as many as 34 students. This research produces: 1) LKPD based on Discovery Learning assisted by Software Tracker which is valid. Based on the research results, the average results of material aspects are 81.33%, learning design aspects are 80% and language aspects are 80%, 2) practicality test results in the one to one stage obtained an average of 93% with a very practical category, 3) the results of the practicality test at the small group stage obtained an average of 87.62% with a very practical category, 4) the field test stage obtained the highest N-Gain value by 64.70% in the high category and the lowest N-Gain value is 35.29% in the medium category.ÃÂ